Privacy awareness among healthcare professionals in intensive care unit: A multicenter, cross-sectional study. Issue 6 (10th February 2023) - Ozdinc, Ahmet; Aydin, Zuleyha; Calim, Muhittin; Ozkan, Ahmet Selim; Bakir, Huseyin; Akbas, Sedat
Abstract : This multicenter, cross-sectional study aimed to determine and examine the privacy awareness and patient rights education of healthcare professionals working in intensive care units (ICUs). The primary purpose of this study was to determine the privacy awareness of healthcare professionals working in the ICU. In addition, the secondary aim was to examine the relationship between patient rights education and awareness scores, as well as to question the need for privacy awareness education. The study population consisted of ICU physicians, nurses, and allied health personnel working in university hospitals, training and research hospitals, state hospitals, and private hospitals in Turkey. The data were collected through a questionnaire prepared by the researchers, including a question set about sociodemographics, a question about patient rights education, and the privacy awareness scale (PAS) scores using online Google Forms. In the results of the study conducted among 569 participants, the mean total PAS score was 38.31 ± 2.54. The PAS score was significantly different according to the occupation. The PAS scores of the nurses were higher than physicians and allied health personnel. The PAS scores differed according to whether the participants had received patient rights education. This study found that nurses were the group with the highest PAS scores among healthcare professionals. In addition, the PAS scores of nurses working in private and training and research hospitals were higher than those of other hospital employees. On the other hand, the lowest scores belonged to university hospitals and receiving patient rights education increased the PAS score of the nurses. This study showed that all enrolled healthcare professionals required in-service training to gain privacy awareness.